The α-synuclein proteostasis network and its translational applications in Parkinson’s disease - Christine M. Lim; Michele Vendruscolo (Proceedings of the National Academy of Sciences, 2026)
Parkinson’s disease (PD) is a debilitating neurodegenerative condition that results in a loss of mobility and muscle control. A neuropathological hallmark of PD is the presence of aberrant inclusions, known as Lewy pathology, of which α-synuclein (α-Syn) is a major component. The accumulation of α-Syn may be due to an imbalance in the proteostasis system regulating α-Syn. To investigate this hypothesis, we delineated the proteostasis network (PN) of α-Syn in the human substantia nigra at the proteomic and transcriptomic level. We then defined an α-Syn proteostasis activity score (PAS) that quantifiably describes the relative activity of the α-Syn PN in promoting or inhibiting α-Syn aggregation. We report a corresponding PAS signature indicative of disease state, age-of-death in PD patients, and brain regional vulnerability to α-Syn aggregation in PD and healthy brains. After establishing the relevance of our network to PD, we developed a transcriptome-derived network model as an operational digital twin of the α-Syn PN in human substantia nigra cells from single-cell data and used it to prioritize candidate targets for PD. We then further showed the application of the α-Syn PN toward facilitating drug repurposing. Overall, this proof-of-concept study illustrates how our computational framework can identify and prioritize putative therapeutic targets and repurposing candidates for PD, providing testable hypotheses for experimental validation.